Evidence for Weyl fermions in a canonical heavy-fermion semimetal YbPtBi - C. Y. Guo (Nature Portfolio, 2018)
Weyl fermions are evidenced in weakly correlated electron systems, but whether they survive strong electron correlations remains obscure. Here, Guo et al. report evidence of the chiral anomaly, topological Hall effect and a cubic temperature dependence of specific heat, suggesting existence of Weyl fermions in a heavy fermion semimetal YbPtBi.